DEMOGRAPHIC CRISIS IN UKRAINE: STATE, CONSEQUENCES AND PROSPECTS OF OVERCOMING IT - KRAVETS, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article analyzes the demographic situation in Ukraine, which has acquired signs of a demographic crisis. There has been an unprecedented decline in Ukraine’s population, which has lost a fifth in the years since independence. The current trends of population decline in the regional context have been studied. It is established that the prospects of depopulation are quite disappointing, given the low overall fertility rate, as well as the predominance of mortality over fertility. The natural movement of the population has been studied, the main causes of its high mortality, especially in working age, due to increased morbidity, in particular the high prevalence of risk factors for noncommunicable diseases, which form more than 80% of mortality in Ukraine, under the influence of endogenous, exogenous and quasi-endogenous factors. The causes of low birth rate, as well as modern features and orientations of reproductive behavior of the population are revealed. In Ukraine, there is a tendency of low life expectancy and population aging compared to some European countries. It is concluded that under such conditions large-scale depopulation will be inevitable. The peculiarities of modern migration processes, in particular labor migration, which can give impetus to alternative migration, have been clarified. The interaction of demographic processes and socio-economic development of the country is determined. Ways to overcome the demographic crisis are a set of demographic measures (organization and conduct of the census, which was not conducted for two decades, the formation of population registers, increasing financial assistance to mothers at birth in accordance with modern requirements, etc.) and socio-economic measures to strengthen reproductive behavior, flexible employment for childbirth and child rearing, improving the level and quality of life of citizens, increasing work motivation in Ukraine, social protection of citizens, etc.
Keywords: demographic crisis; population; birth rate; mortality; natural population movement; life expectancy; population aging; migration